Response diversity in corals: hidden differences in bleaching mortality among cryptic Pocillopora species - Burgess, Scott; Johnston, Erika; Wyatt, Alex; Leichter, James; Edmunds, Peter (Dryad, 2021)
Variation among functionally similar species in their response to
environmental stress buffers ecosystems from changing states. Functionally
similar species may often be cryptic species representing evolutionarily
distinct genetic lineages that are morphologically indistinguishable.
However, the extent to which cryptic species differ in their response to
stress, and could therefore provide a source of response diversity,
remains unclear because they are often not identified or are assumed to be
ecologically equivalent. Here, we uncover differences in the bleaching
response between sympatric cryptic species of the common Indo-Pacific
coral, Pocillopora. In April 2019, prolonged ocean heating occurred at
Moorea, French Polynesia. 72% of pocilloporid colonies bleached after 22
days of severe heating (>8°C-days) at 10 m depth on the north shore
fore reef. Colony mortality ranged from 11% to 42% around the island four
months after heating subsided. The majority (86%) of pocilloporids that
died from bleaching belonged to a single haplotype, despite twelve
haplotypes, representing at least five species, being sampled.
Mitochondrial (open reading frame) sequence variation was greater between
the haplotypes that experienced mortality versus haplotypes that all
survived than it was between nominal species that all survived. Colonies
>30 cm in diameter were identified as the haplotype experiencing
the most mortality, and in 1125 colonies that were not genetically
identified, bleaching and mortality increased with colony size. Mortality
did not increase with colony size within the haplotype suffering the
highest mortality, suggesting that size-dependent bleaching and mortality
at the genus level was caused instead by differences among cryptic
species. The relative abundance of haplotypes shifted between February and
August, driven by declines in the same common haplotype for which
mortality was estimated directly, at sites where heat accumulation was
greatest, and where larger colony sizes occurred. The identification of
morphologically indistinguishable species that differ in their response to
thermal stress, but share a similar ecological function in terms of
maintaining a coral-dominated state, has important consequences for
uncovering response diversity that drives resilience, especially in
systems with low or declining functional diversity.
Please see the README.txt file for metadata and description of R code files
Keywords: Bleaching; colony size; Moorea; Pocillopora; FOS: Natural sciences